2020
DOI: 10.3390/ijerph17103726
|View full text |Cite
|
Sign up to set email alerts
|

Blood Mercury Levels in Children with Kawasaki Disease and Disease Outcome

Abstract: The risk of ethnic Kawasaki disease (KD) has been proposed to be associated with blood mercury levels in American children. We investigated the blood levels of mercury in children with KD and their association with disease outcome. The mercury levels demonstrated a significantly negative correlation with sodium levels (p = 0.007). However, data failed to reach a significant difference after excluding the child with blood mercury exceeding the toxic value. The findings indicate that KD patients with lower sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…However, we founded that KD children with repeated IVIG resistance had higher N%, PCT, and lower ALB, Na + compared with KD children responding to repeated IVIG treatment, which is also con rmed associating with both initial and repeated IVIG resistance in other studies [21][22][23][39][40][41][42][43], indicating more serious in ammation and increased vascular permeability [35,44,45]. It suggested these children may require more aggressive anti-in ammatory therapy.…”
Section: Discussionsupporting
confidence: 66%
“…However, we founded that KD children with repeated IVIG resistance had higher N%, PCT, and lower ALB, Na + compared with KD children responding to repeated IVIG treatment, which is also con rmed associating with both initial and repeated IVIG resistance in other studies [21][22][23][39][40][41][42][43], indicating more serious in ammation and increased vascular permeability [35,44,45]. It suggested these children may require more aggressive anti-in ammatory therapy.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, Chang et al measured blood mercury levels in 85 patients with KD from 2016 to 2020 and examined the association between treatment resistance and coronary artery aneurysms. The results showed no significant differences or association between blood mercury levels and KD outcomes 26 .…”
Section: Discussionmentioning
confidence: 71%
“…Multiple studies have reported hyponatremia as a predictor of IVIG-resistant KD, with a threshold value of 133–135.35 mmol/L of Na 28 31 . This pathogenesis may be attributed to the fact that compared to IVIG-sensitive KD, IVIG-resistant KD results in increased levels of IL-6, TNF-α, and other cytokines 32 , which in turn cause excessive secretion of antidiuretic hormone 33 that leads to increased blood volume and decreased blood Na 34 .…”
Section: Discussionmentioning
confidence: 99%